Augustine on the Transcendent in Music - Walhout, Donald (Philosophy & theology, 1989)
I offer an argument for the claim that there is a transcendent dimension in music. The argument begins with one offered by Augustine in the De Musica, and adds additional support from contemporary discussions in musicology.